Ð£Ñ‡Ð°ÑÑ‚ÑŒ Ð°Ð´Ñ€ÐµÐ½- Ñ‚Ð° Ñ…Ð¾Ð»Ñ–Ð½ÐµÑ€Ð³Ñ–Ñ‡Ð½Ð¸Ñ… ÑÐ¸ÑÑ‚ÐµÐ¼ Ð¼Ð¾Ð·ÐºÑƒ Ð² Ñ€ÐµÐ³ÑƒÐ»ÑÑ†Ñ–Ñ— Ð°ÐºÑ‚Ð¸Ð²Ð½Ð¾ÑÑ‚Ñ– Ð½ÐµÐ¹Ñ€Ð¾Ñ†Ð¸Ñ‚Ñ–Ð² Ð³Ñ–Ð¿Ð¾Ñ‚Ð°Ð»Ð°Ð¼ÑƒÑÐ° Ñ‚Ð° Ñ‚Ð¸Ñ€ÐµÐ¾Ñ‚Ñ€Ð¾Ð¿Ð¾Ñ†Ð¸Ñ‚Ñ–Ð² Ð°Ð´ÐµÐ½Ð¾Ð³Ñ–Ð¿Ð¾Ñ„Ñ–Ð·Ð° Ð¿Ñ‚Ð°Ñ…Ñ–Ð² Ð¿Ñ€Ð¸ Ð´Ñ–Ñ— Ñ…Ñ€Ð¾Ð½Ñ–Ñ‡Ð½Ð¾Ð³Ð¾ Ñ…Ð¾Ð»Ð¾Ð´Ð¾Ð²Ð¾Ð³Ð¾ ÑÑ‚Ñ€ÐµÑÑƒ - Oleksiyenko, N. V.; Pazyuk, L. M.; Buzinska, N. O.; Dzerzhinsky, M. E. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2004)
Choline- and adrenergic brain systems are found to be involved into the adaptation reaction of hypothalamo-pituitary-thyroid system in birds on a long-term cooling due to the stimulating effect.